Dance History and Digital Humanities Meet at the Archives: An Interim Project Report on Dunham's Data. (November 2020) - Bench, Harmony; Elswit, Kate
Abstract : This interim project report addresses the ongoing work of Dunham's Data: Katherine Dunham and Digital Methods for Dance Historical Inquiry. The project centres choreographer Katherine Dunham's transnational circulation, and takes a critical mixed methods approach informed by feminist and anti-racist discussions in the digital humanities in order to explore the questions and problems that make data analysis and visualization meaningful for dance history. Dunham's Data sits on robust datasets that we have manually curated from currently undigitized sources – an iterative and evaluative process that approaches these archives and the histories that they contain from a granular perspective. This update contextualizes our particular conjunction of archival and digital methods within dance history's precedents for curating data, and talks through our own datasets as tools for dance historical analysis in terms of Dunham's global legacy.